Circannual rhythms in Arctic charr (Salvelinus alpinus) - Pelko, Magdalena Maria (UiT Norges arktiske universitet, 2023)
The Arctic charr (Salvelinus alpinus) is a true arctic species and is considered to be the northernmost freshwater fish. Since this species is being known for its great variability in size, phenotype, colour, ecology and history, some of them are landlocked (which stay in freshwater all their life) and others are anadromous (they undertake summer migrations to sea and then they come back to freshwater). Some fish from salmonid family (to which Arctic charr also belongs) as rainbow trout (Oncorhynchus mykiss) and Atlantic salmon (Salmo salar) display circannual rhythms in maturation and reproduction. Circannual rhythms are endogenous biological oscillations which underlie a wide range of seasonal processes. Reproductive activities are then well-timed to period of year, where spring and summer conditions favor rearing offspring. During winter metabolic rates may be reduced which results in weight loss. Photoperiod is one of most well-known cues, which shows the least year to year variability and is a major source of predictive environmental information in controlling various seasonal activities. Better understanding of fish physiology makes it easier to breed fish in aquaculture and lower the mortality of fish. For this study more than 200 fish were put in 8 tanks (2 tanks for each of four treatments) in SNP (simulated natural photoperiod), SP (short photoperiod with 6 hours of light and 18 hours of dark), IP (intermediate photoperiod) and LL (constant photoperiod with 24 hours of light). The first hypothesis was about growth and reproductive status of research animals being under circannual control. The second one hypothesized that these circannual characteristics are dependent upon photoperiod. The last one suggested that circannual rhythm characteristics are dependent on the life history of an animal. It was shown that although Arctic charr is a very variable species, there is a rhythmicity in weight, length and reproductive status, which are not damped in any of all these 4 treatments. Photoperiod has an ...